2000
DOI: 10.1007/bf02723661
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of rural pre-school children of Haryana state

Abstract: The present investigation was conducted on 90 rural pre-school children (1-3 years) in summer and winter from arid (Bhiwani), semi-arid (Hisar) and wet (Kurukshetra) zones of Haryana State, India. Mean daily food intake of cereals, pulses, green leaf vegetables, other vegetables, roots and tubers, milk products, fats and oils, sugar and jaggery and fruits was found lower than their respective recommended dietary intake (RDI) in summer season whereas in winter season mean daily food intake of milk and milk prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In the study conducted by Jood S et al, 8.89% of preschool children had pale conjunctiva. According to NFHS-3 prevalence of anemia in India was 69.5% and in Karnataka was 70.4% [11].…”
Section: Resultsmentioning
confidence: 99%
“…In the study conducted by Jood S et al, 8.89% of preschool children had pale conjunctiva. According to NFHS-3 prevalence of anemia in India was 69.5% and in Karnataka was 70.4% [11].…”
Section: Resultsmentioning
confidence: 99%
“…The recorded Hb levels were found at par with standard value (11.5 g/dl) as given by WHO (2001) in both groups after supplementation. Likewise, Jood, Bishnoi, and Sehgal (2000) also reported an improvement in the Hb level of the anemic school going children after supplementation of biscuits. Similarly, Diaz, Rosado, and Allen (2003) observed that the iron absorption capacity was found more in the anemic children who were supplemented with iron-rich food supplement.…”
mentioning
confidence: 79%
“…According to their findings, none of the food product showed a strong positive correlation between price and quality, and only two showed a moderate positive correlation. They concluded that the higher the price, the higher the quality is not supported regarding food product categories [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relationship between these two variables significantly varies from country to country [12]. Jood et al [13], examined thirty-two food product categories in terms of the quality and price relationship. According to their findings, none of the food product showed a strong positive correlation between price and quality, and only two showed a moderate positive correlation.…”
Section: Introductionmentioning
confidence: 99%